Impact of fossil fuel emissions on atmospheric radiocarbon and various applications of radiocarbon over this century - Graven,HD (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Radiocarbon analyses are commonly used in a broad range of fields, including earth science, archaeology, forgery detection, isotope forensics, and physiology. Many applications are sensitive to the radiocarbon ((14)C) content of atmospheric CO2, which has varied since 1890 as a result of nuclear weapons testing, fossil fuel emissions, and CO2 cycling between atmospheric, oceanic, and terrestrial carbon reservoirs. Over this century, the ratio (14)C/C in atmospheric CO2 (Δ(14)CO2) will be determined by the amount of fossil fuel combustion, which decreases Δ(14)CO2 because fossil fuels have lost all (14)C from radioactive decay. Simulations of Δ(14)CO2 using the emission scenarios from the Intergovernmental Panel on Climate Change Fifth Assessment Report, the Representative Concentration Pathways, indicate that ambitious emission reductions could sustain Δ(14)CO2 near the preindustrial level of 0‰ through 2100, whereas "business-as-usual" emissions will reduce Δ(14)CO2 to -250‰, equivalent to the depletion expected from over 2,000 y of radioactive decay. Given current emissions trends, fossil fuel emission-driven artificial "aging" of the atmosphere is likely to occur much faster and with a larger magnitude than previously expected. This finding has strong and as yet unrecognized implications for many applications of radiocarbon in various fields, and it implies that radiocarbon dating may no longer provide definitive ages for samples up to 2,000 y old.